Comparison of instep kicking by non-preferred leg among various states and intensities in young football players - Bjelica, D.; Georgiev, G.; Popovic, S. (Acta Kinesiologica, 2011)
This research was aimed at gaining relevant knowledge about important differences with respect to compare accuracy of instep kicking by non-preferred leg depending on the different intensity (optimal and maximal) in a resting state, and in a state of fatigue. The sample included 20 respondents whose characteristics were: age (yrs) 16.7±0.47, height (cm) 178.91±4.26, and body weight (kg) 71.52±5.13. The sample of variables contained four measures that defined accuracy of instep kicking by preferred leg in various occasions: with optimal and maximal intensities and in a resting state and a state of fatigue respectively. The results of the measuring were analyzed by means of a statistical procedure labeled a significance test of two arithmetic means conducted on independent samples or popularly known a t-test. Based on the results it was affirmed that significant differences occur in the case of almost all the variables as it was expected and it was concluded that various intensities affect, while various states don`t affect the accuracy of instep kicking by non-preferred leg at a significance level of p=.05.